The Analysis of the Factors Which Affect the Building Costs in Indonesia - Taufik Dwi Laksono (Salehan Institute of Higher Education, 2017)
Buildings are the kind of facility needed by everyone. The accuracy in determining the amount of costs required to build a building has become a challenge for all parties involved in the process. This study aims to determine the factors affecting the cost of a building. By using four independent variables, i.e. floor area, number of floors, foundation depth, and project implementation time, and one dependent variable in the form of a contract value of the building project, an analysis to determine the factors that influence the cost of a building has been made. Using 81 samples in several cities in Indonesia and multiple linear regression of stepwise method, the results show three factors that significantly affect the cost of building projects. They are floor area, number of floors, and project implementation time. This is indicated by tcount for floor area of 12.770, tcount for the number of floors of 46.05, and tcount for project implementation time of 2.321.